In a Seminar on Budget Mix Variances. - Manes, Rene P. (The Accounting Review, 1968)
The article reports on a seminar on budget mix variances. After having attended to his instructor patiently for several quarters and after a review of the literature, Peter Griffin, second-year management student, overcame his own natural reticence and the spring lethargy spreading over the campus and questioned the general applicability of budget mix variances in gross profit analysis. His challenge invigorated discussion for almost a whole period. Whether he is right or not, this communique claims to take no position. Instead here is a scenario of the exchange he maneuvered, and it will be left to the reader to judge for himself the merit of Griffin's position. The point of computing a budget mix variance is that net income or contribution margin will differ from expectations as the quantity increases if the mix changes. The one occasion for which it seems reasonable to compute mix for budgets or sales is when production planning is pretty well locked in or fixed at some level and when later on deliberate substitution between products takes place at that level. Then there has to be a decision to change the mix and there should be a variance to measure the effect of that decision.